Mechano-Regulation of Trabecular Bone Adaptation Is Controlled by the Local in vivo Environment and Logarithmically Dependent on Loading Frequency - Scheuren, Ariane C.; Vallaster, Paul; Kuhn, Gisela A.; Paul, Graeme R.; Malhotra, Angad; Kameo, Yoshitaka; Müller, Ralph (Frontiers in Bioengineering and Biotechnology, 2020)
It is well established that cyclic, but not static, mechanical loading has anabolic effects on bone. However, the function describing the relationship between the loading frequency and the amount of bone adaptation remains unclear. Using a combined experimental and computational approach, this study aimed to investigate whether trabecular bone mechano-regulation is controlled by mechanical signals in the local in vivo environment and dependent on loading frequency. Specifically, by combining in vivo micro-computed tomography (micro-CT) imaging with micro-finite element (micro-FE) analysis, we monitored the changes in microstructural as well as the mechanical in vivo environment (strain energy density (SED) and SED gradient) of mouse caudal vertebrae over four weeks of either cyclic loading at varying frequencies of 2Hz, 5Hz, or 10Hz, respectively or static loading. Higher values of SED and SED gradient on the local tissue level led to an increased probability of trabecular bone formation and a decreased probability of trabecular bone resorption. In all loading groups, the SED gradient was superior in the determination of local bone formation and resorption events as compared to SED. Cyclic loading induced positive net (re)modeling rates when compared to sham and static loading, mainly due to an increase in mineralizing surface and a decrease in eroded surface. Consequently, bone volume fraction increased over time in 2Hz, 5Hz and 10Hz (+15%, +21% and +24%, p≤0.0001), while static loading led to a decrease in bone volume fraction (-9%, p≤0.001). Furthermore, regression analysis revealed a logarithmic relationship between loading frequency and the net change in bone volume fraction over the four week observation period (R2=0.74). In conclusion, these results suggest that trabecular bone adaptation is regulated by mechanical signals in the local in vivo environment and furthermore, that mechano-regulation is logarithmically dependent on loading frequency with frequencies below a certain threshold having catabolic effects, and those above anabolic effects. This study thereby provides valuable insights towards a better understanding of the mechanical signals influencing trabecular bone formation and resorption in the local in vivo environment.